Hourly calculation method of building energy demand for space heating and cooling based on steady-state heat balance equations - Monstvilas, Edmundas; Stankevicius, Vytautas; Karbauskaitė, Juratė; Burlingis, Arunas; Banionis, Karolis (Journal of Civil Engineering and Management, 2012)
Correct evaluation of solar heat gains through fenestration into the rooms has a great impact on energy demand calculations for buildings. This article presents an hourly energy demand calculation method for heating and cooling, which considers the fact that the solar radiation flow passed through the transparent fenestration into the rooms is not adequate to the thermal energy flow. This method considers that the thermal energy flow in the rooms transformed from solar thermal radiation depends on the short-wave thermal radiation absorption coefficient of internal surfaces of the rooms. The value of short-wave thermal radiation absorption coefficient forms a considerable impact on the flow of thermal energy gains in the room. The presented method differs from others on that score that it considers additionally physical lows, according to which the solar short-wave thermal radiation energy admitted into the room is converted into the thermal energy. This hourly method enables precise calculating the hourly mean of indoor temperature and energy demand for heating and cooling of the buildings during the day.